Telemedicine Teaching for Everyone? Comparing Responses of Medical Students and Residents with a Shared Curriculum - Kristi VanDerKolk; Shamsi Daneshvari Berry; Lisa Graves (Telemedicine Reports)
Introduction: The COVID-19 pandemic forced rapid increases in the use of telemedicine, which requires a different skillset than in-person visits. Both medical students and residents required urgent training in telemedicine to utilize the technology for patient care. This study compares evaluation outcomes using the same shared national curriculum for medical students and family medicine residents at the same institution. Methods: Medical students and family medicine residents at Western Michigan University Homer Stryker M.D. School of Medicine completed and evaluated the Society of Teachers of Family Medicine Telemedicine Task Force national curriculum on best practices and foundations within the realm of telemedicine. A Mann–Whitney analysis was performed on Likert scale questions. Results: Medical students had significantly greater knowledge, skill, or attitude acquisition from Module 1, the basics of telemedicine, than family medicine residents. There were no significant differences in knowledge, skill, or attitude acquisition in Module 2, 3, 4, or 5. Discussion: The results from this single-institution sample of medical students and family medicine residents using a shared telemedicine curriculum illustrate important differences from the national data. Unlike the national data, there was a significant difference in knowledge, skill, or attitude acquisition in Module 1, while there was no difference in knowledge, skill, or attitude acquisition in the remaining four modules. Our results indicate changing utility of the telemedicine modules based on previous and ongoing experience. Learners of multiple levels find utility in a shared curriculum in teaching novel concepts.